Optical solitons and modulation instability analysis to the quadratic-cubic nonlinear Schrödinger equation - Inc, Mustafa; Aliyu, Aliyu Isa Isa; Yusuf, Abdullahi; Baleanu, Dumitru (Nonlinear Analysis: Modelling and Control, 2018)
This paper obtains the dark, bright, dark-bright, dark-singular optical and singular soliton solutions to the nonlinear Schrödinger equation with quadratic-cubic nonlinearity (QC-NLSE), which describes the propagation of solitons through optical fibers. The adopted integration scheme is the sine-Gordon expansion method (SGEM). Further more, the modulation instability analysis (MI) of the equation is studied based on the standard linear-stability analysis, and the MI gain spectrum is got. Physical interpretations of the acquired results are demonstrated. It is hoped that the results reported in this paper can enrich the nonlinear dynamical behaviors of the PNSE.